Reductionism and Practicality - Smith, Kevin; Vul, Edward (Cosmos and History: The Journal of Natural and Social Philosophy, 2014)
<!–[if gte mso 9]> <![endif]–> <!–[if gte mso 9]> <![endif]–>Like most domains of science, the study of the mind has been tackled at many scales of analysis, from the behavior of large groups of people (economics and ecology), to the diffusion of ions across cellular membranes (molecular biology and biophysics). At each of these scales, researchers often believe that the critical phenomena of interest, and the most powerful explanatory constructs and mechanisms, reside at their scale of analysis, with finer scales argued to be incapable of predicting the interesting phenomena, while coarser scales are purported to miss critical mechanistic subtleties. Here we argue by analogy that, for better or worse, researchers at all scales are correct: phenomena at each scale of analysis are intractable from other scales; thus, while reductionism is a useful scientific goal, it will not obviate the need for macroscopic research, constructs, and formalisms. <!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> <!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>